Menilik Gerakan Misioner dalam Kepemimpinan Petrus Octavianus, serta Kontribusinya Terhadap Gereja dan Bangsa - Nico Pabayo Gading; Sugihyarto Sugihyarto; Romelus Blegur (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M), 2022)
Not a few people hold leadership positions, but only a handful of people take part as leaders in missionary movements, even though the church has a missionary call that must be fulfilled. It was at this point that Petrus Octavianus appeared in his life and works to show himself as one of the few people whose figure reflects a missionary movement. With his missionary movement, Petrus Octavianus moved across borders to proclaim Christ. The research method used is a qualitative method with a narrative study approach. The results of this research show that a missionary leader can produce works that tend to be unexpected. This is reflected in the experience of Petrus Octavianus as a religious and national figure with a multitude of achievements that have received much appreciation as a manifestation of his theological life journey which was made possible by the grace of the Lord Jesus Christ.